Causes of Ammonium Nitrate Explosions and Handling Mechanisms – Case Study of the 2020 Beirut Lebanon Explosion - Dyota Arkka Gatya; Rudy Laksmono W; Imam Supriyadi (CV. AFDIFAL MAJU BERKAH, 2024)
Ammonium nitrate (AN) is a chemical that is widely used in industry, for example as fertilizer in agriculture, explosives in military and civilian applications (for example in mining) or as a basic ingredient in solid propellants. However, as a dangerous chemical, storing ammonium nitrate can cause problems if not properly. The characteristics of AN have been studied extensively that pure AN is stable at room temperature but can explode when mixed with impurities in a closed space or in the presence of a heat/flame source nearby. This was proven in the explosion disaster at the Port of Beirut, Lebanon in 2020. This article was written using a systematic literature review (SLR) approach, where the data used came from articles published on Google Scholar, DOAJ, Emerald, Springer, and Science Direct with relevant keywords according to the topic. This article aims to evaluate and find out the causes of the ammonium nitrate explosion disaster in Beirut, as well as provide an analysis of suggestions for handling mechanisms so that a similar incident does not happen again. Evaluation of the cause of the explosion at the Port of Beirut, with fire/heat burning down part of the warehouse. An that was stored in a port warehouse mixed with other goods caused a large explosion which was started by a small fire in the warehouse. The explosion caused the death of 220 people, injured 6,500 people, formed a crater 140 meters deep and an earthquake measuring 3.3 on the Richter scale. This explosion is classified as the third most destructive urban explosion of all time, after the atomic bombs on Hiroshima and Nagasaki at the end of World War II. As a precaution, proper handling and storage of AN is required in accordance with international regulations. To reduce the potential danger of explosions without causing significant risks, this is done through an appropriate disposal mechanism.